Characteristics of split-step skills of the world's top athletes in badminton. - Hidehiko Shishido; Takeshi Nishijima (PLoS ONE)
Objective The purpose of this study was to quantitatively measure the split-step skills of the world's top badminton players to clarify the characteristics underlying these skills when moving into the forehand position in the rear court. Methods We analyzed the four best ranking players (1st to 4th) in the men's singles competition at the World Badminton Federation (BWF) World Championships 2023, a world tournament whose match videos are available online. Analysis 1 was conducted to determine the location of the players' feet on the court when performing a split-step while moving to the forehand rear court, as well as the width of the stance and the reaction time from that stance to taking the first step. To define the characteristics of top athletes, the split-step skill performance of these athletes was evaluated during play. Analysis 2 was used to determine whether the performance of the split-step when moving to the forehand rear court varied depending on the position of the opposing player. Results Analysis 1 showed that the split-step position was gathered close to the base, with an average split-step reaction time of 0.25 s and a split-step stance width comprising 50% of the players' height. These results were similar among all top players evaluated. Analysis 2 showed that the difference in the number of shuttlecocks that hit the opponent's backhand rear court (LR) affected their degree of split-step skill. Conclusion In this study, we quantitatively measured the split-step skills of the world's top badminton athletes and clarified the characteristics of their positioning into the forehand rear court during active play. Herein, movement and performance analysis using match videos available online was used to gain novel insights into the performance of these athletes.